The effect of COVID-19 on a Major Trauma Network. An analysis of mechanism of injury pattern, referral load and operative case-mix. Issue 3 (March 2021) - Sephton, B.M.; Mahapatra, P.; Shenouda, M.; Ferran, N.; Deierl, K.; Sinnett, T.; Somashekar, N.; Sarraf, K.M.; Nathwani, D.; Bhattacharya, R.
Highlights: Introduction Comparison of 12 week COVID-19 lockdown period and the same time period in 2019 Aims: to evaluate changes in both mechanism and diagnoses of injuries presenting to the orthopaedic department during this lockdown period, as well as to observe any changes in operative case-mix during this time. Methodology 5 NHS Foundation Trusts included in research contributing to the Major Trauma Network of North West London. Giving a huge number of referrals studied (>6000 referrals); thus giving an acute representation of trauma and injury patterns during the lockdown period. All data received from one trauma system with consistent data coding. Results Referral Numbers ○ Overall referral numbers fell by 35.3% in lockdown period compared to 2019 Mechanism of Injury ○ All injury patterns reduced in number ○ Falls remained proportionally the most common injury pattern ○ Proportion of sports related accidents fell during lockdown ○ Whilst the proportion of pushbike related accidents increased ○ Mechanism injury analysis by age group also presented in manuscript (Table 1) Injury Pattern ○ Remained consistent with reduced amounts of non-bony injury presentations (Table 2) Number of Operations ○ Total number of operations fell by 38.8% during lockdown ○ Operative Case Mix ○ Operative case mix remained fairly similar between lockdown period and 2019 ○ Fewer spinal operations were performed during the lockdown period ○ The proportion of NOF# operations to overall operations increased during the lockdown period Rates of Operative Intervention ○ Rates of operative intervention for NOF# and Ankle fractures (open and closed injuries) remained similar between both study periods ○ Rates of operative intervention for distal radius fractures were reduced – suggesting a more conservative approach Conclusions The nationwide lockdown has led to a decrease in emergency orthopaedic referrals and associated injuries. There has been a change in mechanism of injuries and a reduction in the overall number of acute trauma procedures performed. This study should provide some insights to facilitate policy writing during the recovery phase and may help guide decision making regarding orthopaedic trauma care if lockdown measures are re-instated or similar emergency pandemics are encountered in the future. Abstract: Purpose: The aim of this study was to evaluate changes in both mechanism and diagnoses of injuries presenting to the orthopaedic department during this lockdown period, as well as to observe any changes in operative case-mix during this time. Methods: A study period of twelve weeks following the introduction of the nationwide "lockdown period", March 23 rd – June 14 th, 2020 was identified and compared to the same time period in 2019 as a "baseline period". A retrospective analysis of all emergency orthopaedic referrals and surgical procedures performed during these time frames was undertaken. All data was collected and screened using the 'eTrauma' management platform (Open Medical, UK). The study included data from a five NHS Foundation Trusts within North West London. A total of 6695 referrals were included for analysis. Results: The total number of referrals received during the lockdown period fell by 35.3% (n=2631) compared to the same period in 2019 (n=4064). Falls remained proportionally the most common mechanism of injury across all age groups in both time periods. The proportion sports related injuries compared to the overall number of injuries fell significantly during the lockdown period (p<0.001), however, the proportion of pushbike related accidents increased significantly (p<0.001). The total number of operations performed during the lockdown period fell by 38.8% (n=1046) during lockdown (n=1732). The proportion of patients undergoing operative intervention for Neck of Femur (NOF) and ankle fractures remained similar during both study periods. A more non-operative approach was seen in the management of wrist fractures, with 41.4% of injuries undergoing an operation during the lockdown period compared to 58.6% at baseline (p<0.001). Conclusion: In conclusion, the nationwide lockdown has led to a decrease in emergency orthopaedic referrals and procedure numbers. There has been a change in mechanism of injuries, with fewer sporting injuries, conversely, there has been an increase in the number of pushbike or scooter related injuries during the lockdown period. NOF fractures remained at similar levels to the previous year. There was a change in strategy for managing distal radius fractures with more fractures being treated non-operatively.